Role of biofilm in catheter-associated urinary tract infection - Trautner, Barbara W. (2004)
The predominant form of life for the majority of microorganisms in any hydrated biologic system is a cooperative community termed a “biofilm.” A biofilm on an indwelling urinary catheter consists of adherent microorganisms, their extracellular products, and host components deposited on the catheter. The biofilm mode of life conveys a survival advantage to the microorganisms associated with it and, thus, biofilm on urinary catheters results in persistent infections that are resistant to antimicrobial therapy. Because chronic catheterization leads almost inevitably to bacteriuria, routine treatment of asymptomatic bacteriuria in persons who are catheterized is not recommended. When symptoms of a urinary tract infection develop in a person who is catheterized, changing the catheter before collecting urine improves the accuracy of urine culture results. Changing the catheter may also improve the response to antibiotic therapy by removing the biofilm that probably contains the infecting organisms and that can serve as a nidus for reinfection. Currently, no proven effective strategies exist for prevention of catheter-associated urinary tract infection in persons who are chronically catheterized.